Ordering and interactions between Cl adatoms on Cu(111) and their influence on the local electronic properties as measured by STM and STS - TORSNEY, SAMUEL; BOLAND, JOHN; NAYDENOV, BORISLAV (My University, 2017)
We present a scanning tunneling microscopy/spectroscopy study of compressed Cl adlayers on Cu(111) under ultrahigh-vacuum conditions. We describe a rational scheme to assign Cl adatoms to different surface sites. The dominant electronic state visible in scanning tunneling spectroscopy (STS) corresponds to an anti-bonding interaction between the Cl adlayer and the copper surface. This state was observed to be 200meV higher in energy at hcp sites compared to fcc sites, and it is attributed to the greater charge transfer to Cl adatoms at hcp sites. Although there was no STS signature associated with bridging sites, the presence of bridging Cl adatoms along the periphery of fcc domains caused a shift in the energy of the interface state in the latter. These results shed important light on the ordering and interaction between Cl adatoms on Cu(111) and their influence of the local electronic structure of the surface.
PUBLISHED
Keywords: Scanning tunneling microscopy; Nanoscience & Materials; ADSORPTION; CHEMISORPTION; CHLORINE CHEMISORPTION; DISSOCIATIVE ADSORPTION; DOMAIN WALLS; ELECTRONIC-STRUCTURE; SCANNING TUNNELLING MICROSCOPY (STM); SURFACE ELECTRONIC-STRUCTURE